Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J. E.; Jimenez, B.; Suarez, F. (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
The following values have no corresponding Zotero field: pub-location: 445 UNION BLVD, STE 230, LAKEWOOD, CO 80228-1259 USA publisher: SOC RANGE MANAGEMENT
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J E; Jimenez, B; Suarez, F (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

LAS BOÑIGAS DE VACA, EL ENCESPEDADO DE POA BULBOSA, Y LA DIVERSIDAD EN UN PASTIZAL DE DEHESA - Malo, J E Juan E; Suarez, F; Vaca, L A S Boñigas D E; Poa, E L Encespedado D E; Diversidad, Y L A; Un, E N; Dehesa, Pastizal D E (Pastos, 1996)
The interactions of cattle dung pats, the Poa bulbosa Turf and the number of species in a pasture is analyzed at a 10x10 cm scale, through a four-year monitoring of 50 dung pats. Dung pats elimínate the Poa bulbosa Turf, and its recovering takes more than four years. The rest of the species are also displaced by dung pats, but they colonize the gaps much faster. Thus, the number of species by sample is significantly smaller on dung pats the first year after deposition (5-4 vs. 10-8), not distinguishable the second and third years (9-2 vs. 10-0 and 9-3 vs. 8-0), and significantly higher the fourth year after depo- sition (13-8 vs. 10-7). These results seem to be associated to the competitive behaviour of Poa bulbosa. This species colonizes the gaps slowly, but it is able to displace other species from them. The effect of the process is relatively small for the whole pasture due to the small área covered by dung pats. However, due to the uneveness of dung deposi- tion it can contribute to the development of pasture gradients of composition and diver- sity associated to grazing.
Keywords: Central Spain; centro de españa; competencia; competition; dinámica de pastizales; disturbance; dung; excrementos; herbivores; herbívoros; pasture dynamics; perturbación